Statin prescription disparities in patients with breast cancer and diabetes for primary cardiovascular disease prevention - Yang, Alicia B.; Mhango, Grace; Kong, Chung Yin; Lin, Jenny J.; Wisnivesky, Juan P.; Leiter, Amanda (Frontiers in Oncology, 2024)
BackgroundThis brief report examines statin prescription trends for primary cardiovascular disease (CVD) prevention in breast cancer (BC) survivors with diabetes, a large population at particularly high CVD risk.MethodsA population-based, retrospective cohort study was conducted using Surveillance, Epidemiology, and End Results (SEER) cancer registry data linked to Medicare claims. We identified women with preexisting diabetes who were diagnosed with stage 0–III primary BC between 2008 and 2017 without preexisting CVD. We assessed statin prescription rates over time and also examined differences in statin prescription rates according to patient sociodemographic characteristics. Using a multivariate logistic regression adjusted for sociodemographic and clinical variables, independent predictors of statin prescription were identified.ResultsOf 8,423 BC patients with diabetes without preexisting CVD, 5,698 (68%) had a statin prescription. Statin prescriptions increased over time (BC diagnosis year 2008–2009: 65%, 2010–2011: 67%, 2012–2013: 66%, 2014–2015: 69%, 2016–2017: 70%; p = 0.01) and differed by age (66–69: 66%, 70–74: 70%, 75–79: 69%, ≥80: 65%; p < 0.01) and race (White: 68%, Black: 62%, Latina: 66%, Other: 72%; p < 0.01). In a multivariate analysis, race (Black vs. White: OR 0.80, 95% CI: 0.68–0.95) remained a predictor of statin prescription.ConclusionIn older early-stage BC survivors, statin prescriptions increased over time and varied by age, race, and BC stage. These findings can potentially inform strategies to improve guideline-concordant statin prescriptions in a group at high risk for CVD and reduce disparities.